1986
DOI: 10.1017/s0022215100099370
|View full text |Cite
|
Sign up to set email alerts
|

Secretory otitis media—Evidence for an inherited aetiology

Abstract: SummaryIn a study to determine whether or not there is a familial or hereditary pre-disposition to develop secretory otitis media (SOM), the parents of 73 children with presistent SOM and 35 controls were examined clinically, and abnormalities of the tympanic membrane (TM) noted. Analysis of the findings suggests that heredity plays a large part in determining a child's likelihood of developing SOM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…Familial factors have also been shown to be important in the aetiology of OM [5,17,18]. We confirmed that a family history of ear infection was a predictor of effusion in this population.…”
Section: Risk Factors For Presence Of Effusionsupporting
confidence: 80%
“…Familial factors have also been shown to be important in the aetiology of OM [5,17,18]. We confirmed that a family history of ear infection was a predictor of effusion in this population.…”
Section: Risk Factors For Presence Of Effusionsupporting
confidence: 80%
“…On the other hand, some investigators have reported the course of SOM to be more favourable in girls than in boys, and tympanic membrane scarring to be more common in parents of children with chronic SOM than in parents of healthy children. indicating that the existence of some hereditary factor can not be excluded (28,29). Although our rAOM children had significantly more SOM periods of several months' duration than the "healthy" children, none of them had middle ear secretion at 10-y follow-up.…”
Section: Discussionmentioning
confidence: 73%
“…A trend for SOM to heal more rapidly in girls than in boys has also been observed (Fiellau-Nikolajsen, 1979a;. Another observation is that the parents of children with long-lasting SOM, more fre quently than parents of children without ear problems, have significantly more scars in the tympanic membrane consistent with former episodes of otitis media (Rockley & Rhys Evans, 1986).…”
Section: Selected Congenital and Hereditary Factorsmentioning
confidence: 77%